Epigenetic modification of gene expression in colorectal carcinogenesis - Krakowczyk, Łukasz; Strzelczyk, Joanna Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2007)
Colorectal carcinoma is a common malignancy in both males and females. Current treatment modalities include surgery, chemotherapy and irradiation of rectal lesions. Despite these interventions, however, there isconsiderable variance in treatment success. This has been observed in same-stage tumours treated with standardized surgical and chemotherapeutic schedules. It has been postulated that these variations arise due to inherent differences in the tumour characteristics, in particular their molecular profiles. In colorectal carcinogenesis disturbances different from genetic changes, called epigenetic regulations, are also taken into consideration. Epigenetics is defined as modifications of the genome, heritable during cell division, that do not involve a change in the DNA sequence. In humans, the fundamental epigenetic process is DNA methylation and histone modifications. It was demonstrated that certain colorectal cancers originate on the basis of this epigenetic disorder. Hypermethylation was discovered among others in promoters of the following genes – p16, p14, APC, MGMT and MLH1.